Apropriações do método intuitivo de Pestalozzi para o ensino de saberes elementares matemáticos em periódicos brasileiros do final do século XIX e início do século XX - Ferreira, Jefferson dos Santos (2017)
In this text are presented results of a research whose objective was analyze the appropriations of the intuitive method of Pestalozzi for the teaching of elementary mathematical knowledge in Brazilian periodicals of late of XIX and early of XX centuries. The theoretical contribution came from the use of Chartier (2003) to talk about appropriation, Valente (2015) about the elementary mathematical knowledge, Ragazzini (2001) about historical sources and Pestalozzi (1889, 2003) aiming an understanding about the intuitive method. In reading the works of Pestalozzi it was identified in relation the intuitive method started of elements of number, form and word, aiming the development of the child’s faculties or capacities that he had intuition as a foundation, and was based on perception, observation, use of the senses, in the graduality of teaching and sought to assist in the development of the child as a human person. The resources used Brazilian periodicals of late of XIX and early of XX centuries found in the digital repository of UFSC and that had some reference to Pestalozzi, method or some the principles. As results, can be emphasize a circulation of Pestalozzi in these periodicals, since it was referenced in publications of eight Brazilian states: Alagoas, Amazonas, Bahia, Minas Gerais, Paraná, Rio de Janeiro, Rio Grande do Norte and São Paulo. To indentify appropriation, understood as use or interpretation, were presented at a first moment those that in the articles had explicit references to Pestalozzi, and at a second moment, the articles that brought the intuitive method or some the principles. It is also worth noting that in the periodical Pestalozzi was pointed out as a forerunner of modern pedagogy, active school, natural education, and culture of the senses etc, all this refers to the intuitive method. He was also taken as an example of master and authority in Education. In relation to the elementary mathematical knowledge, were identified appropriation about the contents of fractions, count, sum and calculations called elementary arithmetical knowledge, geometric solids and drawing called elementary geometric knowledge. It is also emphasize that for the application of method intuitive, the elementary mathematical knowledge were indicated objects such as: Parker Letters, mechanical counters and geometric solids.